(untitled) - Bratton, John (Basingstoke, Hampshire, 1992)
This book introduce the perspectives on Japanization. Trade unions and change at work, patterns of change. The motor components company Japanization in large-batch production...
Keywords: Quản trị công nghiệp,Industrial management; Nhật Bản,Japan